2019
DOI: 10.1002/ptr.6355
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide enhances sensitivity of K562/ADR chronic myeloid leukemia cells to doxorubicin through PI3K/Akt pathway

Abstract: Costunolide, a sesquiterpene lactone, a small molecular monomer extracted from Inula helenium, has been reported to possess antiproliferative effects on several cancer cell lines. The current study was designed to evaluate the effect of costunolide on sensitivity of K562/ADR chronic myeloid leukemia cells to doxorubicin. The antiproliferative effect of costunolide was assessed by CCK‐8 assay. Flow cytometry and Western blot were used to examine the mechanisms of antileukemia action. Costunolide dramatically en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
(21 reference statements)
2
9
0
Order By: Relevance
“…We determined that elevated p21 expression induced by costunolide treatment in A431 may be involved in the suppression of cell proliferation via induction of cell cycle arrest (Figure 4). Consistent with our findings, several studies revealed that costunolide treatment induced the G 2 /M phase of cell cycle arrest via elevation of p21 expression [45,47,48].…”
Section: Discussionsupporting
confidence: 92%
“…We determined that elevated p21 expression induced by costunolide treatment in A431 may be involved in the suppression of cell proliferation via induction of cell cycle arrest (Figure 4). Consistent with our findings, several studies revealed that costunolide treatment induced the G 2 /M phase of cell cycle arrest via elevation of p21 expression [45,47,48].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the p21-dependent, p-53-independent pathway has been shown to be associated with an increased apoptosis, as is evident in our system, in contrast to the p21-dependent, p53-dependent pathway that promotes the translocation of p21 from the nucleus to the cytoplasm thus determining an anti-apoptotic effect absent in our study [22]. It is known from previous studies that compounds isolated from Inula species may have antiproliferative effect on a different leukaemia cells [51][52][53][54][55][56][57][58][59] but, as far as we know, only one work describing the activity of Inula extract on an acute myeloid leukaemia (KG1a cell line) has been reported [60]. This work highlighted the effect of Inula compounds on induction of apoptosis by the mitochondria-dependent pathway.…”
Section: Resultssupporting
confidence: 48%
“…It is known from previous studies that compounds isolated from Inula species may have antiproliferative effect on a different leukaemia cells [51][52][53][54][55][56][57][58][59] but, as far as we know, only one work describing the activity of Inula extract on an acute myeloid leukaemia (KG1a cell line) has been reported [60]. This work highlighted the effect of Inula compounds on induction of apoptosis by the mitochondria-dependent pathway.…”
Section: Resultsmentioning
confidence: 82%
“…The NF-κB pathway drives MDR1 expression using the common agonist phorbol ester 12-O-tetradecanoyl-13acetate (TPA). LY294002 treatment down regulated the expression of NF-κB, which indicates that the inhibition of the PI3K/AKT signaling pathway modulated the downregulation of MDR1 expression 105,106 . The modulation of P-gp phosphorylation by AKT kinase or the direct interaction of P-gp with inhibitors cannot be excluded 107 .…”
Section: P-gpmentioning
confidence: 98%